Multi-omics study and ncRNA regulation of anti-BmNPV in silkworms, Bombyx mori: an update - Fan, Yi-Xuan; Andoh, Vivian; Chen, Liang (Frontiers in Microbiology, 2023)
Bombyx mori silkworm is an important economic insect which has significantly contribution to the improvement of the economy. Bombyx mori nucleopolyhedrovirus (BmNPV) is a vitally significant purulent virus that impedes the sustainable and stable development of the silkworm industry, resulting in substantial economic losses. In recent years, with the development of biotechnology, transcriptomics, proteomics, metabolomics, and related techniques have been used to select BmNPV-resistant genes, proteins, and metabolites. The regulatory networks between viruses and hosts have been gradually clarified with the discovery of ncRNAs, such as miRNA, lncRNA, and circRNA in cells. Thus, this paper aims to highlight the results of current multi-omics and ncRNA studies on BmNPV resistance in the silkworm, providing some references for resistant strategies in the silkworm to BmNPV.